MAKNA DAN FUNGSI PAMALI MASYARAKAT SUKUPASER KECAMATAN LONG IKIS KABUPATEN PASER (THE MEANING AND FUNCTION OF PRACTICAL COMMUNITY INTEREST PASER DISTRICT LONG ACTS PASER) - Siti Aisyah (Universitas Lambung Mangkurat, 2020)
AbstractThe Meaning and Function of Practical Community Interest Paser DistrictLong Acts Paser. This study uses a descriptive method, a qualitative form with anethnographic approach to communication. The purpose of ethnographiccommunication in this research is to study or study language in relation to thecustoms or habits of a society. The data source is pamali text which researchersgathered from six informants. While research data are words, phrases or sentencesin pamali that show meaning and function. The techniques used are participantobservation, in-depth interviews, and records. Data analysis is done bytranscribing data, selecting data, identifying data, classifying data, andconcluding data to determine the meaning and function of the guardian. Based onthe results of the analysis it can be concluded that pamali in the Paser communityhas the deepest (implied) meaning. The meaning contained in the Pamali societyis teaching the values of education and norms that exist in the community by wayof rebuking, advising and reminding to behave in accordance with the norms andforms of moral preservation, attitude and behavior. In this research, the functionof pamali is adjusted to the purpose of someone conveying pamali. The pamalifunction, namely (1) functions to educate in the form of morals, behavior,compassion, respect for fellow creatures created by God, maintain solidarity,strengthen the faith, and avoid feeling lazy, (2) functions as a form of selfprotectionin the form of safety, protecting women pregnant and children.Key words: pamali, Paser tribe, meaning, function, sociolinguistics AbstrakMakna dan Fungsi Pamali Masyarakat SukuPaser Kecamatan Long IkisKabupaten Paser. Penelitian ini menggunakan metode deskriptif, bentuk kualitatifdengan pendekatan etnografi komunikasi. Tujuan etnografi komunikasi dalampenelitian ini ialah mengkaji atau mempelajari bahasa dalam hubungan denganadat-istiadat atau kebiasaan suatu masyarakat. Sumber data adalah teks pamaliyang peneliti himpun dari enam informan. Sedangkan data penelitian ialah katakata,frasa atau kalimat dalam pamali yang menunjukan makna dan fungsi. Teknikyang digunakan adalah observasi partisipan, wawancara mendalam, dan rekam.Analisis data dilakukan dengan mentraskripsi data, seleksi data, identifikasi data,pengklasifikasi data, dan menyimpulkan data untuk mengetahui makna dan fungsipamali. Berdasarkan hasil analisi dapat disimpulkan bahwa pamali dalammasyarakat Paser memiliki makna terdalam (tersirat). Adapun makna terdapatdalam pamali masyarakat Paser adalah mengajarkan nilai-nilai pendidikan dannorma-norma yang ada di masyarakat dengan cara menegur, menasehati danmengingatkan agar bersikap sesuai dengan norma-norma dan bentuk penjagaanmoral, bersikap dan berprilaku. Dalam penelitian ini fungsi pamali disesuaikandengan tujuan seseorang menyampaikan pamali. Adapun fungsi pamali, yaitu (1)berfungsi mendidik berupa moral, perilaku, rasa kasih sayang, menghargaisesama makhluk ciptaan Tuhan, menjaga solidaritas, penebal keimanan, danmenghindari rasa malas, (2) berfungsi sebagai bentuk perlindungan diri berupamenjaga keselamatan, melindungi perempuan hamil dan anak-anak.Kata-kata kunci:pamali,suku Paser, makna, fungsi, sosiolinguistik